2018
DOI: 10.3390/cryst8020069
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alginate from Chilean Lessonia nigrescens and MWCNTs on CaCO3 Crystallization by Classical and Non-Classical Methods

Abstract: Abstract:In our crystallization experiments, the influence of alginate from Chilean Lessonia nigrescens and functionalized multi-walled carbon nanotubes (MWCNTs) was tested through electrocrystallization (EC) and gas diffusion (GD) methods on the crystal growth of calcium carbonate (CaCO 3 ) and their possible stabilization of proto-structures in amorphous CaCO 3 (ACC) state through pre-nucleation clusters (PNC) essays with automatic potentiometric titrations were performed. CaCO 3 crystals obtained in the in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
(61 reference statements)
0
4
0
Order By: Relevance
“…It was also found that the potentiometric response curves begin to stabilize by increasing the temperature, and the effect of the system decreases the variation between each point measured in the EC of CaOx. In addition, we reported that anionic MWCNTs also acted as efficient inhibitors in the in vitro CaCO 3 crystallization …”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…It was also found that the potentiometric response curves begin to stabilize by increasing the temperature, and the effect of the system decreases the variation between each point measured in the EC of CaOx. In addition, we reported that anionic MWCNTs also acted as efficient inhibitors in the in vitro CaCO 3 crystallization …”
Section: Resultsmentioning
confidence: 97%
“…In addition, we reported that anionic MWCNTs also acted as efficient inhibitors in the in vitro CaCO 3 crystallization. 31 Herein, MWCNT-IA was a better inhibitor template than the well-known organic citrate, which was used to inhibit the EC of CaOx at 37 and 60 °C. The morphology (Figure 4) and hydrated crystal forms (Figure 5) of CaOx obtained via EC using citrate and all the MWCNTs by applying a 9 mA current for 5 min in a closed system at 37 or 60 °C were analyzed by SEM and XRD, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Abundant functional groups have been found in sodium alginate, such as carboxyl and hydroxyl groups, which can crosslink with cations [ 11 , 12 ]. Sodium alginate reacts with divalent cations such as Ca(II), Ba(II) and Sr(II) to form insoluble hydrogels, which are crosslinked to form a reticular structure called the “egg box”, and the crosslinking pathway is the exchange between the sodium ions of α-L-guluronic acid and divalent ions [ 13 , 14 ]. In addition, alginate beads can be easily recovered [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sánchez and coworkers [2] started from the same assumption regarding the role exerted by biological functional molecules during the crystallization of carbonates. They introduced the effect of inorganic precursor species (IPS), namely amorphous phases and pre-nucleation clusters (PNCs) in order to understand the interactions between organic and inorganic phases, and discussed the effect of plain carbon nanotubes (CNTs) and alginate-functionalized CNTs on the nucleation and growth of carbonates using electrochemical (EC) and gas diffusion (GD) techniques.…”
mentioning
confidence: 99%